Warehouse inventory management through simulation - Jin, Xilong (2009)
Research has been carried out to study the issue of multi-items inventory replenishment of a warehouse which demand and lead time are stochastic. In this research, analytical models are limited in terms of adequately treating uncertainties and dynamic aspects of inventory problem. Simulation methodology has been adopted to optimize inventory level and improve the inventory management in this warehouse. Firstly, previous research in inventory management and a brief overview of classical models of stochastic inventory theory are provided. Secondly, a data analysis methodology is presented for the simulation inputs. Thirdly, simulation method and inventory replenishment policies for the warehouse system are researched. At the end, this thesis is summarized with analysis of the simulation output and finished with the future research and concluding remarks that are drawn from the research.